Praktik Filantropi Jalanan Sebagai Upaya Penguatan Ekonomi Umat: (Studi Kasus Sistem Bagi Hasil di Masjid Baitul Hamdi Nagari Tabek dalam Perspektif Ekonomi Islam) - Diana Putri, Meli; Fahlefi, Rizal; Lutfi, Ahmad (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to analyze the practice of street-based philanthropy carried out by the community of Baitul Hamdi Mosque in Nagari Tabek, Pariangan District, Tanah Datar Regency, from the perspective of Islamic economics and Minangkabau customary values. The research employs a qualitative approach with data collected through interviews, observations, and documentation. The findings reveal that the fundraising activities conducted on public roads are voluntary and transparent, based on mutual agreement between mosque administrators and community members. The revenue-sharing schemes of 60:40 and 50:50 reflect principles of fairness and mutual consent, in line with Islamic muamalah values. Theologically, this practice embodies the spirit of ta‘awun (mutual assistance), ihsan (beneficence), and amanah (trustworthiness). Socioeconomically, it functions as a grassroots mechanism for community empowerment. Minangkabau cultural values such as bulek kato dek mufakat (consensus-based decision-making) and barek samo dipikua, ringan samo dijinjiang (shared responsibility) further strengthen collective solidarity and accountability in managing communal funds. Thus, the street-philanthropy model practiced at Baitul Hamdi Mosque represents a community-based Islamic socio-economic system rooted in local wisdom, fully aligned with the principles of maqasid al-shariah in promoting justice, public welfare, and communal well-being.